X-ray fluorescent analysis using synchrotron radiation: Subjects of research - Trunova, V. A.; Zvereva, V. V. (Journal of structural chemistry, 2016)
The brief review has been presented about the application of X-ray fluorescent analysis using synchrotron radiation (storage ring VEPP-3, BINP SB RAS) for determination of elemental composition of the samples of different nature–biological and geological samples, objects of environment, archeological objects, and new materials. The feature of the presented research is the employment of the unique properties of synchrotron radiation, which allow analyzing samples of small mass (of the order of several milligrams), and also scanning core of bottom sediments with high resolution (less than 1 mm) that is not practical to realize by traditional analysis methods.